2019
DOI: 10.1007/s42452-019-1149-1
|View full text |Cite
|
Sign up to set email alerts
|

Potential biocontrol and superlative plant growth promoting activity of indigenous Bacillus mojavensis PB-35(R11) of soybean (Glycine max) rhizosphere

Abstract: Disease control using microbes that exhibit beneficial effects on plants to strengthen the host is a foremost requirement in agriculture. The aim of the present study is to search for an effective biocontrol agent against Rhizoctonia solani endowed with high plant growth potential. A total of 95 bacterial strains were isolated from the soybean plant rhizosphere and screened in vitro against R. solani by dual culture technique, revealing that strain PB-35(R11) was the most efficient for controlling R. solani wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
6
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(12 citation statements)
references
References 43 publications
3
6
0
Order By: Relevance
“…Hassan et al [51], Akhtar et al [52], and Niu et al [53] documented plant growth promotion, the reduction of metal toxicity, and the defense response-ability of Bacillus cereus. Similar plant growth promotion and biocontrol activities of Bacillus mojavensis were reported by Prajakta et al [37] and Rath et al [54]. Despite many studies that have reported on plant growth promotion of several crops using rhizosphere bacteria, soil contamination by various salts and toxic substances could limit the efficacy of this PGP bacteria.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…Hassan et al [51], Akhtar et al [52], and Niu et al [53] documented plant growth promotion, the reduction of metal toxicity, and the defense response-ability of Bacillus cereus. Similar plant growth promotion and biocontrol activities of Bacillus mojavensis were reported by Prajakta et al [37] and Rath et al [54]. Despite many studies that have reported on plant growth promotion of several crops using rhizosphere bacteria, soil contamination by various salts and toxic substances could limit the efficacy of this PGP bacteria.…”
Section: Discussionsupporting
confidence: 70%
“…PGPR, which produces IAA, induces primary root elongation and the formation of lateral roots that enables the plant to absorb more nutrients. In a previous study, IAA that produces Bacillus mojavensis PB-35(R11), which is antagonistic to Rhizoctonia solani, produced 29 µg/mL of IAA [37], whereas the Bacillus spp. used in our study produced a higher amount.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In a similar study, Palmieri et al [41] screened four antagonist bacteria Rhanella aquatilis, Pseudomonas fluorescens, Serratia marcescens, and B. amyloliquefaciens against Foc and Fsp of wilt and root rot causing chickpea and have proved their complementary capacities to solubilize tricalcium phosphate, chitinase production, and IAA production. Our result was also in accordance with those reported by Prajakta et al [72] who reported that Bacillus mojavensis PB-35(R11) exhibited phosphate solubilization, hydrogen cyanide, chitinase, IAA, and siderophores production, which may be involved in antifungal activity against Rhizoctonia solani and in promoting plant growth of soybean. Lim et al [73] recently reported a B. velezensis strain capable of producing antifungal volatile and agar-diffusible metabolites that inhibited mycelial growth of several plant pathogenic fungi.…”
Section: Discussionsupporting
confidence: 93%
“…Multiple split applications of mineral nitrogenous fertilizers can reduce N losses [6] and increases nitrogen use efficiency [7]. Greater soil N accumulation is due to mineralization of soil organic matter or greater root exploration in fertilized plants than unfertilized plants [8]. Nitrogen losses from the soil-plant system are large, leading to low fertilizer N use efficiency when N application is not synchronizing with crop demand.…”
Section: Introductionmentioning
confidence: 99%